Menu Cycles - Clayton, Alfred; Almony, John; Rutgers, The State Univ., New Brunswick, NJ. Curriculum Lab. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
The curriculum guide for commercial foods instruction is designed to aid the teacher in communicating the importance of menu cycles in commercial food production. It also provides information about the necessary steps in getting food from the raw form to the finished product, and then to the consumer. In addition to providing information on how to design and use menu cycles, the text also discusses the selection, handling, storage, and preparation of fruits and vegetables, meats, poultry, eggs, seafood, and rice and pasta. Units are included on cost control and the role of a balanced diet in the menu cycle. A 60-page section provides recipes for large quantities and a 15-page section of unit tests concludes the document. (NJ)
Availability: Vocational-Technical Curriculum Laboratory, Rutgers, The State University, Building 4103, Kilmer Campus, New Brunswick, New Jersey 08903 (Order No. F-59, $3.00).
Sponsoring Agency: New Jersey State Dept. of Education, Trenton. Div. of Vocational Education.
ERIC Note: Photographs will not reproduce in microfiche.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cooking Instruction; Curriculum Guides; Food Service; Foods Instruction; Nutrition Instruction; Occupational Home Economics; Secondary Education; Tests; Menu Cycles; Recipes; Guides, General